Wahbah Zuhaili's Understanding of the Verses on Adultery: A Review of Al-Tafsir Al-Munir - SAM, Muhamad Nurbaden (UIN Sunan Gunung Djati Bandung, 2023)
Adultery has recently become a major problem faced by mankind, especially whether it is prostitution or abnormal-sex considering that this ugliness is among the oldest on earth, this crime is very difficult to deal with and even trying to reduce it is very difficult. This is made clear by the reading of the text of the Qur'an by the mufasir, so that in this study it is hoped that it will be able to trigger Wahbah Zuhaili's best interpretation of zina and its relevance to the Criminal Code in Indonesia. This research uses qualitative research methods, namely research that contains written data such as documents or other texts that are relevant to the topic of discussion, this written data is usually in the form of words or actions and not in the form of numbers (numeric). The collection of sources in this research was obtained by means of library research or book surveys. In this technique, there are three stages that must be done. First, inventorying the verses on adultery. Second, read, browse, and compile interpretations of wAhbzh zuhaili. Third, describe and analyze the interpretation of these adultery verses, so that comprehensive and holistic research findings or results can be obtained.